Comparative assessment of exfoliated gingival cells in healthy individuals and chronic periodontitis patients with and without tobacco chewing habit: A cytomorphometric study - Sachita S Naik; Aarati Nayak; Vijaylakshmi Kottrashetti; Akanksha Bhatt (Wolters Kluwer Medknow Publications, 2022)
Background: Cytomorphometry is the analysis of the morphometry of exfoliated cells. Studies on exfoliated gingival epithelial cells in chronic periodontitis were not evident on the literature search. In the backdrop of this information, we were inspired to conduct a cytomorphometric study. Aim: The aim of the study is to correlate the nuclear area (NA), cytoplasm area (CA), and the nuclear: cytoplasm ratio (N/C) in the gingival cells of healthy individuals, patients with chronic periodontitis, and chronic periodontitis patients who are tobacco chewers. Materials and Methods: Ninety subjects, aged 35-45 years, were categorized into three equal groups of 30 each. Group I had individuals with healthy gingiva, Group II patients with chronic periodontitis without any deleterious habits, while Group III patients with chronic periodontitis and tobacco chewing habit. Exfoliated gingival cells were stained with Papanicolaou stain. Analysis of cells was done using binocular light microscope under ×40 and i-progress® image analyzer software. Results: There was statistically significant increase in CA in all the groups, but NA and N/C ratio did not show any statistical significant difference. When Group II was compared with Group III, we found significant correlation of CA with pocket probing depth and clinical attachment loss (CAL) in Group II. Similarly, we also found a correlation of CA and N/C with pocket depth and CA with CAL in Group III. Conclusion: The results suggest that molecular level changes occur in the cells. Cytomorphometry can be used to analyze the cellular changes in chronic periodontitis patients even before clinical signs manifest. Hence, it can be used as an investigative tool.